Examination of stocking density and marketing strategies in a commercial production environment - Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The influence of stocking density (7.4 or 6.6 sq ft per pig) and marketing strategy (0, 1, or 2 sorts before closeout) was examined in a commercial production environment. No interaction between stocking density and marketing strategy was observed. Higher stocking density had no negative effects on growth performance or carcass characteristics. The major advantage of one or two sorts was a reduction in sort loss of $.27/cwt carcass ($.52/pig) compared to no sorts. No differences were found between one and two sorts under the packer matrix used in this study.
Keywords: Swine; Stocking density; Growth marketing; Carcass characteristics